Help Me To Help You : Strategies for Working Effectively with Governments - Kutchava, Kakhaber; Tevzadze, Maia (World Bank, Washington, DC, 2012)
In development work, the authors all have heard many words of advice for effective work with governments. But succeeding at policy work is easier said than done. This paper describes how International Finance Corporation's (IFC's) Georgia Corporate Governance Project was able to support the process of reforms in a fast-paced, challenging political and administrative environment and amid shifting government priorities. The purpose of this smart lesson is to share some of the challenges faced in work with government and to provide useful tips for effective policy work.